Comparison of butterfly diversity in natural and regenerating forest in a biodiversity conservation site at maragamuwa, Sri Lanka - Mihindukulasooriya, M.; Ranawana, K.; Majer, Jonathan (International Network for Natural Sciences, 2014)
Knowledge of species composition and diversity of butterflies offers great benefits for nature conservation and environmental monitoring. Butterfly species richness and diversity were studied at a biodiversity conservation site at Maragamuwa, Sri Lanka from July 2009 to February 2010 using the fixed distance line transect method. A total of 4968 butterflies belonging to the super families Papilionoidea and Hesperioidea, representing six families and 83 species were recorded during the study period. Of these 83 species, 73 were recorded from the natural forest, while 60 species were recorded from the regenerating forest. The highest numerical abundance of butterflies was recorded from the regenerating forest and the highest species diversity occurred in the natural forest. These observations suggest that the short term monitoring of butterfly assemblages provide monitoringtool for the habitat conservation.